Syncretic constructions with the pronominal adverb «как» in the Russian language: determination of grammatical status - A. V. Sineleva; A. S. Zaitseva (Вестник Самарского университета: История, педагогика, филология)
The article is devoted to the study of the syncretic constructions with a pronominal adverb «как» in the Russian language. These constructions are analyzed in the lexico-grammatical aspect in comparison with introductory sentences and subordinate clauses. The material for the study consists of the texts of printed and electronic media included in the National Corpus of the Russian Language (NCRL). During the study, based on a diachronic approach, the classifications of constructions with a pronominal adverb «как» presented in the authoritative publications of the Russian language grammar are analyzed. As a result, within the framework of structural-semantic classification, a conclusion is made about the possibility of classifying constructions with an adverb «как» a subordinate clause, which makes it possible to minimize transitional cases while differentiating certain syntactic categories.